Industrial Policies vs Public Goods under Asymmetric Information - Hevia, Constantino; Loayza, Norman; Meza-Cuadra, Claudia (World Bank, Washington, DC, 2017)
This paper presents an analytical framework that captures the informational problems and trade-offs that policy makers face when choosing between public goods (for example, infrastructure) and industrial policies (for example, firm- or sector-specific subsidies). After a discussion of the literature, the paper sets up the model economy, consisting of a government and a set of heterogeneous firms. It then presents the first-best allocation (under full information) of government resources among firms. Next, uncertainty is introduced by restricting information on firm productivity to be private to the firm. The paper develops an optimal contract (which replicates the first best), consisting of a tax-based mechanism that induces firms to reveal their true productivity. As this contract requires high government capacity, other, simpler policies are considered. The paper concludes that providing public goods is likely to dominate industrial policies under most scenarios, especially when government capacity is low.